Síndrome de Kleine-Levin. Caso clínico y revisión del tema - Aguilera O., Ledda; Díaz S., Mario; Mena U., Boris; Erazo A., Sandra; Núñez F., Juan Cristóbal (Revista Hospital Clínico Universidad de Chile, 2009)
Episodic hypersomnia, compulsive excessive eating and erotic behaviour, with schizophrenic- like mental symptoms are the hallmarks of the rare Kleine–Levin syndrome. Many patients may not necessarily fulfill minimum criteria described for diagnosis. We report a 19 years young man with incomplete presentation the Kleine–Levin syndrome and briefly reviewed the most relevant aspects of this disorder, its epidemiology, clinical symptoms and complementary diagnostic examinations. Known therapeutic options and prognosis are also discussed.